2020
DOI: 10.3390/bs10050082
|View full text |Cite
|
Sign up to set email alerts
|

Italian Adaption of Self-Perceived Employability Scale: Psychometric Properties and Relations with the Career Adaptability and Well-Being

Abstract: The recent transformation of the workplaces and labor market, characterized by rapid technological changes, social and economic instability, has greatly influenced the construction of people’s career paths. These paths cannot be viewed more as linear, but multifaceted and unstable. In organizational context, the psychological contract has changed from long term to short term. In this scenario, the construct of employability becomes central: people need to maintain and improve their ability to be attractive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 120 publications
0
20
0
2
Order By: Relevance
“…These processes are in fact necessary to establish a successful TA and determine VCP positive outcomes. With COVID-19 giving rise to global growth in the adoption of VC platforms, it is more likely that therapists are going to be increasingly relying on VCTs [ 87 ]. Initial studies have indicated that therapists, after familiarizing themselves with the VCP and VCTs, might increase their confidence in using such technologies and the quality of their TA and TR [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…These processes are in fact necessary to establish a successful TA and determine VCP positive outcomes. With COVID-19 giving rise to global growth in the adoption of VC platforms, it is more likely that therapists are going to be increasingly relying on VCTs [ 87 ]. Initial studies have indicated that therapists, after familiarizing themselves with the VCP and VCTs, might increase their confidence in using such technologies and the quality of their TA and TR [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is a characteristic of societies where innovation predominates, such as the current one we live in. Moreover, according to recent research, flexibility is an essential construct to integrate work teams, to lead people in organizations, and to maintain adequate levels of health and well-being [36,38,39]. Similar to other scales, RS-10 has good internal consistency (α = 0.866), with the factor referring to self-determination showing a Cronbach's α = 0.843 and the factor relating to adaptability revealed a Cronbach's α = 0.813.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the CCT, career adaptability refers to an employee's readiness to confront foreseen work-related challenges and also the preparedness to tackle the unknown work-related challenges that may arise owing to changes in work and working conditions (Lodi et al, 2020;Savickas, 1997). For an employee to able to do so, the adaptive resources namely, concern, control, curiosity and confidence must be activated (Johnston, 2018;Rossier, 2015;Savickas, 2013).…”
Section: Career Adaptability Work Resources and Employee Healthmentioning
confidence: 99%